2009
DOI: 10.2460/javma.234.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of rabies in skunks in Texas

Abstract: Information on the epidemiology of rabies in skunks may be useful in planning and implementing local, state, and national rabies control and prevention campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 7 publications
3
34
0
Order By: Relevance
“…In our study per 7 years of the data showed that animal bite were commoner with adult age group (>15 years age group) as they are considered to be the most agile group. Study conducted by Shelton K [4] and Oertli et al [13] similar finding were reported..…”
Section: Discussionsupporting
confidence: 77%
“…In our study per 7 years of the data showed that animal bite were commoner with adult age group (>15 years age group) as they are considered to be the most agile group. Study conducted by Shelton K [4] and Oertli et al [13] similar finding were reported..…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, circulation areas of the lineages had only limited overlaps, although we could not identify any obvious natural barriers restricting virus spread (Figure 1). Local perpetuation of RABV is also supported by surveillance records which describe outbreaks of skunk rabies as limited foci with increased disease incidence but irregular local geographic spread [6,43,44]. Ecological studies demonstrated that skunks reach higher concentrations and live more sedentarily in proximity to humans, where they can find a variety of food.…”
Section: Discussionmentioning
confidence: 95%
“…However, no SCSK isolates from Mexico are available in GenBank and our archives. Moreover, surveillance records indicate that SCSK has been absent in southern Texas along the Mexican border for many years [2,43]. These observations suggest that arid landscapes of this area and the Rio Grande River represent barriers for virus spread.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-exposure prophylaxis does not eliminate the need for medical care following a potential rabies exposure, but simplifies the protocol and eliminates the need for administration of human rabies immune globulin. 10 …”
mentioning
confidence: 99%